CHARACTER EDUCATION VALUE ANALYSIS IN COLLECTION OF STUDENTS - Riana Dwi Lestari; Reka Yuda Mahardika; via Nugraha (IKIP Siliwangi, 2019)
Education must be adapted to the development of the times so that the academics are required to innovate by utilizing the sophistication of technology as a source of learning, learning media, and teaching and learning process. The development of globalization has an impact on the character of children today who are considered alarming. This can be seen from the development of personality and social development that is not in accordance with religious norms, cultural norms, and social norms prevailing in society. Children tend to be so selfish that they don't like to work together, can't respect their parents or teachers, often they are trapped in the world of crime and drugs. Efforts to instill the values of character education in children in the millennial era can be done by integrating subjects through technology, for example in learning Indonesian language children are assigned to memca poems, short stories, or novels which contain elements of moral values contained in literary works on the Internet. The formulation of the problems in this study are as follows: a) What are the values of character education contained in the short stories of IKIP Siliwangi students? b) What character education values are most contained in the short stories of IKIP Siliwangi students? This research is a qualitative study using descriptive analytical methods. Judging on the basis of methods and objectives, this research includes research and development.